2022
DOI: 10.22541/au.164257194.40766010/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Amelioration of endothelial dysfunction by sodium glucose co-transporter 2 inhibitors: pieces of the puzzle explaining their cardiovascular protection

Abstract: Sodium glucose co-transporter 2 inhibitors (SGLT-2i’s) significantly improve cardiovascular outcome in both diabetic and non-diabetic patients. Preclinical studies suggest that SGLT-2i’s directly affect endothelial function in a glucose-independent manner. The effects of SGLT-2i’s include reduction of oxidative stress and inflammatory reaction in endothelial cells. Furthermore, SGLT2i’s have been shown to restore endothelial-related vasodilation and to regulate angiogenesis. The favorable cardiovascular effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…8H). The effect of eNOS activity and NO production was stronger with empagliflozin, which may be due to additional off-target effects of empagliflozin on eNOS ( 53 ). These findings suggested that empagliflozin alleviates ALDH2*2 -induced oxidative stress and NO reduction via the NHE-1/AKT/eNOS pathway.…”
Section: Resultsmentioning
confidence: 99%
“…8H). The effect of eNOS activity and NO production was stronger with empagliflozin, which may be due to additional off-target effects of empagliflozin on eNOS ( 53 ). These findings suggested that empagliflozin alleviates ALDH2*2 -induced oxidative stress and NO reduction via the NHE-1/AKT/eNOS pathway.…”
Section: Resultsmentioning
confidence: 99%